2006
DOI: 10.1002/hec.1097
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health: does prenatal care make a difference?

Abstract: This research attempts to close an important gap in health economics regarding the efficacy of prenatal care and policies designed to improve access to that care, such as Medicaid. We argue that a key beneficiary-- the mother-- has been left completely out of the analysis. If prenatal care significantly improves the health of the mother, then concluding that prenatal care is 'ineffective' or that the Medicaid expansions are a 'failure' is premature. This paper seeks to rectify the oversight by estimating the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 58 publications
(102 reference statements)
6
70
0
Order By: Relevance
“…Access to good health care during pregnancy is essential for mothers' health and development of her unborn child (10,31). In some instances, healthy behaviours after delivery and parenting skills are acquired during pregnancy (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to good health care during pregnancy is essential for mothers' health and development of her unborn child (10,31). In some instances, healthy behaviours after delivery and parenting skills are acquired during pregnancy (31).…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, healthy behaviours after delivery and parenting skills are acquired during pregnancy (31). Accessing formal health system during pregnancy increases the chance of using skilled attendant at birth and this may contribute to good health of a child in the first year of life (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is obvious that the determinants of maternal and infant health are closely related, there are very few works where the issue of maternal and infant health is considered jointly (Winikoff, 1988;Conway and Kutinova, 2006). Moreover, most of the economic literature (both theoretical and empirical, likewise in developed and developing countries) focuses on infant health almost completely ignoring the issue of maternal health.…”
Section: Related Literaturementioning
confidence: 96%
“…In contrast to the 2SLS, a bivariate probit model is an appropriate method for estimating the simultaneous equations model when outcome and impact are binominal variables (Cameron and Trivedi, 2005). After the 2SLS confirmed that our instruments are correlated with social trust, but uncorrelated with the error term in the main regression equation, we estimated the bivariate probit with the same set of instrumental variables as in the 2SLS (Conway and Kutinova, 2006). Table 1 reports summary statistics and the simple correlation between the use of banking service indicators and social trust, along with a broad array of household-level as well as country-specific variables.…”
Section: Simultaneous Equations Regression Modelsmentioning
confidence: 99%